The Concept of Nāṣiyah in the Qur'an and Its Relevance to the Phenomenon of Digital Pornography Addiction - Abdul Rahim; Abdul Ghaffar; Arfan Arfan (JIA (Jurnal Ilmu Agama), 2025)
This article aims to explore the concept of nāṣiyah in the Qur'an and explore its relevance to the phenomenon of Digital Pornography addiction. This is motivated by the data that brain damage is one of the things that must be avoided by every human being. Damage to the brain can be caused by various factors, such as collisions, taking drugs, and so on. In addition, there are also causes of decreased to damaged human brain function caused by drug addiction through digital pornography or known as narcolema. This article seeks to explain the impact of narcolema and its relevance to the interpretation of the term nāṣiyah in the Qur'an. This article uses a qualitative method with the type of library research. The data sources used in this research come from books, websites, journals and articles related to the Qur'an, articles about pornography, articles about the brain and studies related to neurology. Thus, the article concludes that nāṣiyah in the Qur'an contains complex dimensions of meaning-theological, ethical, and even symbolic-physiological-that illustrate the relationship between human will, moral control, and the consequences of deviant behavior. The relevance of the term nāṣiyah in the Qur'an to narcotics can be seen from a neuropsychological and spiritual perspective. Narcotics damage brain tissue, including the prefrontal region, resulting in impaired cognitive abilities, impulse control, and decision-making functions. As a result, a person's behavior becomes deviant, loses moral control, and tends to commit acts that damage themselves and others.